Crater detection in multi-ring basins of mercury - Pedrosa, Miriam M. [UNESP]; Pina, Pedro; Machado, Marlene; Bandeira, Lourenço; da Silva, Erivaldo A. [UNESP] (Springer Nature, 2015)
This paper presents the automated detection of impact craters on large regions of Mercury. The processing sequence is composed by three main phases: the first consists on creating the image mosaics of the large areas of interest, the second by finding crater candidates on these mosaics, and finally by extracting a set of features that are used in the classification by SVM-Support Vector Machine in the third phase. The detections are performed on images acquired by the MDIS-NAC camera of MESSENGER probe covering three large basins on Mercury (Rachmaninoff, Mozart and Raditladi).
Keywords: Automatic detection; Image processing; Mercury; Pattern recognition